Refund of State Losses Due to Criminal Acts of Corruption on Problematic Credit at Bank BRI Kediri Branch Office - Ismail, Moch Taufiq; Hafidz, Jawade (UNISSULA Semarang, 2025)
The research aims to be Accountable for Refunding State Financial Losses Due to Criminal Acts of Corruption in Problematic Loans at BRI Bank, Kediri Branch Office, Weaknesses and Solutions in the implementation of accountability for refunding state financial losses due to criminal acts of corruption in Problematic Loans at BRI Bank, Kediri Branch Office. The sociological legal approach method is an approach to studying and exploring legal realities experienced in the field or an approach that is based on problems concerning legal matters and existing realities, using the theory of criminal responsibility and the legal system. The results of the research and discussion are that (1) Accountability for the Return of State Financial Losses Due to Corruption Crimes is proven to impose a prison sentence of 4 (four) years 6 (six) months and a fine of Rp. 100,000,000.00. If the fine is not paid, it will be replaced with a prison sentence of 3 (three) months. Imposing an additional sentence on the Defendant to pay compensation of Rp. 891,177,500. If the convict does not pay compensation within 1 (one) month after the court decision has obtained legal force, his property can be confiscated by the Prosecutor and auctioned to cover the compensation in the event that the convict does not have sufficient property to pay compensation, then he will be punished with imprisonment for 2 (two) years.(2) Weaknesses in the implementation of accountability for the return of state financial losses due to corruption; First, if the fine is not paid, it is replaced with imprisonment for 3 (three) months each, from the decision of the fine, it is possible that the defendants choose a substitute sentence of imprisonment because it is considered too light, which is only 3 (three) months imprisonment, rather than fulfilling the provisions of the fine that must be paid is considered quite large, even though they are able. Second, the application of cumulative penalties for corruption, there needs to be implementing regulations, especially regarding the implementation of fines. Third, the threat of imprisonment and fines together, their implementation (execution) must be carried out by defendants of corruption, especially fines.